(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Banks play a crucial role for the financing of Micro, small and medium-sized enterprises (SMEs). SMEs contribute significantly to employment and growth. SMEs are important for knitting any economic system with society, they were facing numerous challenges such as unavailability of low cost finance and subsidy issues. Despite of challenges ahead Indian SME sector are always ready to consent and obtain new technologies, new business Ideas and automation in industrial and engineering sector. Maharashtra is considered one of the most desired industrial locations in the country for setting up industries. The State has shown rapid industrial growth in the recent years. Micro, Small and Medium Enterprises form an important and growing segment of Maharashtra’s industrial sector. The performance of the commercial banks in Maharashtra State is commendable in terms of spread of banking network, mobilization of deposits, disbursement of credits, penetration of the cooperative movement, etc. Adequate and timely availability of Finance is one of the most important key inputs for any business. This is equally applicable while setting up of a MSME unit by an entrepreneur. Micro, small or medium business owners are generally first time entrepreneurs with very little capital or without capital, need not only technical, marketing and managerial support but also require the much needed seed capital to start the business. Many MSME units also need additional capital for technology up gradation, capacity expansion growth, and marketing and for imports and exports. Banks in India have been providing financial facilities to numerous businesses through their branch offices, regional offices in across the length and breadth of the country In Maharashtra also banks have been providing all forms of financial support to these MSME entrepreneurs. This paper examines the major problems faced by banks in financing of micro and small enterprises in the Nagpur city.